Biochemical and Anthropometric Characterisation of hypertension in Kumasi - Aryee, Christiana (2017)
A thesis submitted in fulfillment of the requirements for the degree of Master of Philosophy in the Department of Molecular Medicine, School of Medical Sciences College of Health,